Strategi Pemasaran Anggrek Di “Ghia Farms” dengan Metode Business Model Canvas dan Analisis SWOT - Pramesty, Alma Dianika; Sulandjari, Kuswarini; Nur’azkiya, Luthfi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Ghia Farms is one of the orchid plant producers that sells cut moon orchids and potted orchids. Moon orchids are in demand by many people from various circles ranging from lovers to business needs. The existence of price competition causes the marketing of moon orchids at Ghia Farms to be less than optimal. The purpose of this research is to see the effectiveness of marketing that is being applied, identify the marketing of orchid plants, analyze strengths, weaknesses, opportunities and threats, and analyze strategies that can be used by Ghia Farms based on the Business Model Canvas. The research method used is descriptive method with qualitative and quantitative approaches. Data were analyzed with ROMI, Business Model Canvas Method, and SWOT. The results showed that Ghia Farms' marketing effectiveness is in the good category but close to the minimum limit with a ROMI value of 10.7 in 2021, and 10.5 in 2022, Ghia Farms has indirectly used the Business Model Canvas method, based on the results of SWOT analysis, Ghia Farms' business strategy is located in quadrant 1 with strategies that can be used, namely Strength and Opportunity (SO) or aggressive strategies, these strategies are expanding the e-commerce used, adding services as new programs such as bazaars or flower exhibitions, improving services by implementing a member system and opening offline stores.